JURIDICAL ANALYSIS OF BORDER AREA LAND REGISTRATION AND CONSOLIDATION FROM AN ECOSYSTEM PERSPECTIVE THE ERA OF FIVE POINT ZERO DESTRUCTION - Ginting, Lilawati; Eddy, Triono (Faculty of Law, Universitas Pekalongan, 2024)
Land Registration and Consolidation is a policy in the agrarian and land sector which in a constitutionalist approach is an obligation of the Government in all dimensions of Government management and administration, public services, and all aspects and dimensions of the National life system. Therefore, the author is determined to present the central theme in this journal, namely with the title